Nypa Fruticans As A Potential Low Cost Adsorbent To Uptake Heavy Metals From Industrial Wastewater - Ali, Md. Yousuf; Rahman, Md. Wasikur; Moniruzzaman, Md.; Alam, Jahangir; Saha, Indrajit; Halim, Md. Abdul; Deb, Anjan; Sumi, Mst. Sumaia Akter; Parvin, Shahanaz; Biswas, Biplob Kumar; Haque, Md. Azizul; Khan, Maksudur R.; et al. (Academi Fora, 2016)
Nypa fruticans locally known as Gol leaves (GL) was demonstrated in the present study as a potential low cost adsorbent for the removal of heavy metals, especially Cr(VI) from aqueous solution. A series of batch tests were conducted and the influence of initial metal ion concentration, contact time, pH of the solution and adsorbent dosage was investigated. The adsorbent was characterized by Fourier transform infrared (FTIR) spectroscopy and Brunauer–Emmett–Teller (BET) to confirm the mechanism of the retention of heavy metals. The adsorption process was found to be strongly pH dependent and a value of 4 was optimized for the utmost recovery. The adsorption isotherm data were fitted with Langmuir equation and the maximum adsorption capacity was found to be 76.92 mg/g. Therefore, GL can be employed as an efficient and cost-effective adsorbent for the removal of heavy metals present in industrial wastewater.